Effect of phytosanitary pruning in populations of Aulacaspis tubercularis Newstead (Hemiptera: Diaspididae) and its natural enemies - López Guillén, Guillermo; Urías-López, Mario Alfonso; Noriega-Cantú, David Heriberto (Revista Mexicana de Ciencias Agrícolas, 2018)
The mango white scale (EBM), Aulacaspis tubercularis Newstead (Hemiptera: Diaspididae), is a pest that damages foliage and decreases the commercial value of mango fruits. Phytosanitary pruning is a cultural practice that can help reduce EBM populations in mango orchards. The objective of this work was to evaluate the impact of phytosanitary prunings in EBM populations and their natural enemies in a mango orchard Ataulfo, in Chiapas, Mexico. The phytosanitary pruning was done after the mango harvest (month of May) and its impact on EBM between December 2013 and May 2014 was evaluated, a period considered to be the one with the highest abundance of EBM populations in Chiapas. It was found that the abundance of colonies and total of scales (females + colonies) was lower in trees with phytosanitary prunings compared to mango trees without pruning. The natural enemies that were observed in trees with pruning and without pruning were identified as Ceraeochrysa sp., Azya sp. and Pentilia sp. No significant differences were detected in the abundance of natural enemies between mango trees with and without phytosanitary pruning.